Design and control of underwater hybrid vehicle capable of performing numerous tasks - Shahani, Kamran; Wu, C.; Persaud, R.; Song, H. (Journal of Naval Architecture and Marine Engineering, 2018)
This paper is about Ocean Strider; an Underwater Hybrid Vehicle that is modified with hybrid (manual and autonomous) control system. The aims concerning this Underwater Hybrid Vehicle are to be competent to operate underwater by using remote control via operator and seek out the user interested objects, and in case of autonomously to be smart, to visually follow and manage a secured position comparable to a motionless target, and to visually follow and move behind a moving target and avoid the hindrances for reliable navigation. Vision is a fundamental root that promotes the underwater robot to execute various tasks autonomously. Ocean Strider is intelligent to explicitly identify and locate objects by specifying from distinct color codes and dimension of the objects and respond accordingly. Multiple experiments have been conducted in the laboratory the robot successfully operates manually and grasp the objects underwater, and the robot can locate and track the objects autonomously, secure a fixed distance to the fixed object and travel onward with the object as it moves.